Formation of stable and responsive collective states in suspensions of active colloids - Tobias Bäuerle (Nature Portfolio, 2020)
Living organisms, like fish and bacteria, frequently change their pattern as a group to cope with environment. Here, Bäuerle et al. reproduce this phenomenon using a synthetic system of controllably interactive colloids to show their collective motions that indicates being close to a critical point.